2020
DOI: 10.1080/02770903.2020.1818774
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of non-adherence to guidelines for the prevention of COVID-19 among young adults with asthma in a region with a high risk of a COVID-19 outbreak

Abstract: Objective: SARS-CoV-2 disease 2019 (COVID-19) is highly contagious and spreads rapidly. The application of preventive measures has proven to be the best strategy to minimize the number of patients and the dissemination of and deaths from COVID-19. The objective of this study was to determine the risk factors that limit the adherence of asthmatic patients to measures that prevent COVID-19 among residents of a region with a high risk of a COVID-19 outbreak. Methods: Through a cross-sectional study, data from 2,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
2
8
0
2
Order By: Relevance
“…Evidently, females were more likely to be willing to adhere to the protective measures against the disease. This finding was supported by several studies [14][15][16][17][18] which all agreed that females were more compliant to health-related guidelines than males. Intuitively, health educators should invest more effort in educating females who would, in turn, act as change agents influencing their social networks.…”
Section: Discussionsupporting
confidence: 60%
“…Evidently, females were more likely to be willing to adhere to the protective measures against the disease. This finding was supported by several studies [14][15][16][17][18] which all agreed that females were more compliant to health-related guidelines than males. Intuitively, health educators should invest more effort in educating females who would, in turn, act as change agents influencing their social networks.…”
Section: Discussionsupporting
confidence: 60%
“…It led many of the participants to see themselves resistant to the disease, which made them less likely to observe health norms. In the study of Vázquez et al, 2020, the results indicated that the misconception that COVID-19 was not associated with asthma played a major role in non-compliance with health guidelines [45]. A Ugandan study on misconceptions and the risk of COVID-19 found that participants believed that men were more susceptible to COVID-19 than women and children [46].…”
Section: Discussionmentioning
confidence: 99%
“…In an interesting study, a cohort of 7000 patients had electronic monitoring of their controller and rescue inhaler use during the pandemic, and increased adherence of 15% was found in the controller medication use [122]. According to the results of a cross-sectional study from Mexico, male sex, active smoking, and the belief that COVID-19 was not more severe in asthma sufferers seemed to favor non-adherence to COVID-19 prevention measures [123]. It is therefore important that health professionals and patients with asthma maintain constant communication regarding the measures that patients must comply with to prevent COVID-19 and the timely use of medications to control their chronic disease.…”
Section: Adherence To Therapymentioning
confidence: 99%